2014
DOI: 10.7455/ijfs/3.1.2014.a4
|View full text |Cite
|
Sign up to set email alerts
|

Popping characteristics of paddy using microwave energy and optimization of process parameters

Abstract: Microwave popping characteristics of a particular variety of paddy were studied using a domestic microwave oven. The experiments were carried out at 4 levels of moisture content (around 13%, 14%, 15% and 16% wb), 3 levels of power (600 W, 850 W and 1000 W) and 5 levels of heating time (40 s, 60 s, 80 s, 100 s and 120 s). A general factorial experiment design was followed, and effect of different treatment combinations on popping percentage and expansion ratio of the paddy was evaluated. The maximum popping per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
(5 reference statements)
2
13
0
Order By: Relevance
“…Sharma and Gujral () also reported higher puffing index with sand roasting of barley than that with microwave heating. In other related studies, it has been mentioned that rapid heating with higher microwave power gave higher puffing yields (Maisont & Narkrugsa, ; Mohapatra & Das, ; Singh & Singh, ; Swarnakar et al, ). Thus, these reported published works to support that rapid heating or preheating of grains facilitates higher magnitude of puffing.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Sharma and Gujral () also reported higher puffing index with sand roasting of barley than that with microwave heating. In other related studies, it has been mentioned that rapid heating with higher microwave power gave higher puffing yields (Maisont & Narkrugsa, ; Mohapatra & Das, ; Singh & Singh, ; Swarnakar et al, ). Thus, these reported published works to support that rapid heating or preheating of grains facilitates higher magnitude of puffing.…”
Section: Resultsmentioning
confidence: 95%
“…Puffing of rice and popping of paddy using microwave energy have been reported by several workers (Devi & Das, ; Maisont & Narkrugsa, ; Mohapatra & Das, ; Swarnakar et al, ). According to them, puffing using microwave energy is convenient and hygienic.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…At higher MWP (up to1,200 W), the puffing yield of khao‐tan tended to increase. Generally, a high MWP would cause a rapid increase in the vapor pressure inside the kernel with resulting in a rapid heating rate which would evaporate the water and build‐up the pressure and expand the grain (Swarnakar, Devi, & Das, ). Joshi et al () also reported the power level significantly affected the puffing yield.…”
Section: Resultsmentioning
confidence: 99%
“…The extended PT at a low MWP level was not recommended due to the shrinkage and drying that occurred during puffing (Joshi et al, ). Swarnakar et al () studied the popping characteristics of paddy and found there was an interaction between MWP and PT, where increasing both factors decreased the expansion ratio. In conclusion, water is a dominant factor in grain expansion, as on heating, the water becomes superheated steam which is the driving force for expansion.…”
Section: Resultsmentioning
confidence: 99%